2013
DOI: 10.1177/1557988313516357
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Psychological Distress on Prostate Cancer Screening in U.S. Military Veterans

Abstract: The benefit of routine prostate cancer screening is currently under debate; however, many experts recommend that men with elevated risk for the disease discuss the potential risks and benefits of screening with their health care team. Psychological factors have been negatively associated with preventive health behaviors such as cancer screenings. The purpose of this study was to investigate the impact of depressive and trauma-related symptoms on prostate cancer screening behaviors and relevant health care perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
14
1
Order By: Relevance
“…These findings are particularly important given the unique sample characteristics of a largely underrepresented group in psycho‐oncology distress screening evaluations—AA males of lower SES. Previous studies have predominately evaluated large community/academic hospitals that include primarily Whites with high proportions of females, and markedly low rates of AAs 21–23 . Understanding the specific needs of AA males with cancer is critical in reducing disparities, as they experience 14% higher incidence rates of all cancers and 33% higher death rates compared to their White male counterparts 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are particularly important given the unique sample characteristics of a largely underrepresented group in psycho‐oncology distress screening evaluations—AA males of lower SES. Previous studies have predominately evaluated large community/academic hospitals that include primarily Whites with high proportions of females, and markedly low rates of AAs 21–23 . Understanding the specific needs of AA males with cancer is critical in reducing disparities, as they experience 14% higher incidence rates of all cancers and 33% higher death rates compared to their White male counterparts 24 .…”
Section: Discussionmentioning
confidence: 99%
“…We Previous studies have predominately evaluated large community/ academic hospitals that include primarily Whites with high proportions of females, and markedly low rates of AAs. [21][22][23] Understanding the specific needs of AA males with cancer is critical in reducing disparities, as they experience 14% higher incidence rates of all cancers and 33% higher death rates compared to their White male counterparts. 24 Almost 70% of males in this cohort had advanced disease (stages III andIV) with 86% reporting elevated physical concerns.…”
Section: Discussionmentioning
confidence: 99%
“…2 In the USA, the estimated lifetime prevalence of MDD is 16%. 3 In addition to its burden of disease, MDD exerts a negative impact on physical health [4][5][6][7] and adherence to medical treatment. 8 9 Second-generation antidepressants (eg, selective serotonin reuptake inhibitors or selective serotonin norepinephrine reuptake inhibitors) are the most commonly used treatments for acute MDD.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature suggests that there are a variety of factors that influence participation in cancer control behaviors, including demographic, situational, and psychosocial factors [1417]. Specifically, research has found that attitudes may reduce patients’ intentions to engage in cancer-related behaviors, such as information seeking [18] and treatment decision making [19].…”
mentioning
confidence: 99%